Association between frailty and hospital-related adverse events in older hospitalised patients: a systematic literature review protocol - Jay Banerjee; Brad Manktelow; Abdullah Alshibani; Faris Alotaibi (BMJ Open)
Introduction Research indicates that older hospitalised individuals are more susceptible to hospital adverse events (AEs). Frailty is a syndrome marked by increased vulnerability, sudden and severe health changes and the risk of adverse outcomes. The majority of the available research puts a limited emphasis on those who live with frailty and examines the relationship between age alone and the occurrence of AEs. This review investigates the association between frailty and the likelihood of hospital AE occurrences in hospitalised older patients.Methods and analysis The proposed systematic review will search Ovid MEDLINE, CINAHL, Scopus and Web of Science databases. Studies that published original data in English using any methodology will be included. A manual search of the final included studies reference list will be made to identify studies that meet the inclusion criteria. If feasible, a meta-analysis will be conducted using the R statistical programme, and results will be visually presented using a forest plot. If there is high heterogeneity and a meta-analysis is not feasible, a narrative synthesis and analysis guided by Cochrane criteria will be conducted, and results will be presented in appropriate tables and figures.Ethics and dissemination No ethical approval will be obtained for this review since it will use secondary published data. The systematic review’s results will be published in a peer-reviewed frailty and geriatrics care-related journal and disseminated in conferences, congresses and scientific meetings.